2006
DOI: 10.1007/s00726-006-0407-x
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging potential of L-proline: evidence from in vitro assays

Abstract: An assessment of the potential of proline to scavenge free radicals was made in a couple of in vitro assay systems, namely graft co-polymerization and autooxidation of pyrogallol. Both these assays are essentially dependent upon free radical mechanisms. Graft co-polymerization involved a ceric (Ce(4+)) ion- or gamma-radiation-induced grafting of methyl acrylate (MA) onto a cellulose backbone. The degree of grafting, measured gravimetrically, was taken as a measure of free radical generation. The gamma-radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(132 citation statements)
references
References 22 publications
5
118
0
2
Order By: Relevance
“…Interestingly, we found that proline was ineffective at protecting cells against superoxide generators such as menadione. Recently, it was reported that proline does not interact with superoxide in vitro [53]. Our cellular studies concur with this finding and suggest that proline exhibits specificity toward H 2 O 2 -induced stress.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, we found that proline was ineffective at protecting cells against superoxide generators such as menadione. Recently, it was reported that proline does not interact with superoxide in vitro [53]. Our cellular studies concur with this finding and suggest that proline exhibits specificity toward H 2 O 2 -induced stress.…”
Section: Discussionsupporting
confidence: 91%
“…High levels of hypoxanthine were also found in the resistant lines of our study (IMP and AMP were not detected). Although the precise role of proline remains unclear, our findings and the above-mentioned reports all point toward proline as a general stress-response metabolite, and it has been demonstrated that proline can act as a free radical scavenger in vitro (56). Hence, in drug-resistant L. donovani lines, increased levels of proline might protect against oxidative stress caused by drug pressure.…”
Section: Discussionsupporting
confidence: 72%
“…The activities of APX (ascorbate peroxidase), MDHAR (monohydro ascorbate reductase) and DHAR (dihydro ascorbate reductase) enzymes, which are the components of ASC-GSH cycle, were significantly enhanced by exogenous proline application in tobacco cultures exposed to salinity stress (Hoque et al 2007). Kaul et al 97 using in vitro studies, showed that exogenously applied l-proline proved to be a potent free radical (particularly ROS) scavenger. Hong et al 91 concluded that the role of proline as a free radical scavenger is more important in alleviating stress than its role as a simple osmolyte.…”
Section: Effect Of Exogenous Proline On Plants Exposed To Temperaturementioning
confidence: 99%